A CAD/CAE integration framework for analyzing and designing spatial compliant mechanisms via pseudo-rigid-body methods. (April 2019) - Bilancia, P.; Berselli, G.; Bruzzone, L.; Fanghella, P.
Abstract: Compliant Mechanisms (CMs) are currently employed in several engineering applications requiring high precision and reduced number of parts. For a given mechanism topology, CM analysis and synthesis may be developed resorting to the Pseudo–Rigid Body (PRB) method, in which the behavior of flexible members is approximated via a series of rigid links connected by spring-loaded kinematic pairs. From a CM analysis standpoint, the applicability of a generic PRB model requires the determination of the kinematic pairs' location and the stiffness of a set of generalized springs. In parallel, from a design standpoint, a PRB model representing the kinetostatic behavior of a flexible system should allow to compute the flexures' characteristics providing the desired compliance. In light of these considerations, this paper describes a Computer-Aided Design/Engineering (CAD/CAE) framework for the automatic derivation of accurate PRB model parameters, on one hand, and for the shape optimization of complex-shape flexures comprising out-of-plane displacements and distributed compliance. The method leverages on the modelling and simulation capabilities of a parametric CAD (i.e. PTC Creo) seamlessly connected to a CAE tool (i.e. RecurDyn), which provides built-in functions for modelling the motion of flexible members. The method is initially validated on an elementary case study taken from the literature. Then, an industrial case study, which consists of a spatial crank mechanism connected to a fully-compliant four-bar linkage is discussed. At first, an initial sub-optimal design is considered and its PRB representation is automatically determined. Secondly, on the basis of the PRB model, several improved design alternatives are simulated. Finally, the most promising design solution is selected and the dimensions of a flexure with non-trivial shape (i.e. hybrid flexure) is computed. This technique, which combines reliable numerical results to the visual insight of CAD/CAE tools, may be particularly useful for analyzing/designing spatial CMs composed of complex flexure topologies.